Answer:
a)
![E(X)=(b^2 -a^2)/(2(b-a))=((b-a)(b+a))/(2*(b-a))=(b+a)/(2)](https://img.qammunity.org/2020/formulas/mathematics/college/yb2zc1iwcqn5asmieg6en2gs1xmf2tvv81.png)
b)
![Var(X) =E(X^2) -[E(X)]^2](https://img.qammunity.org/2020/formulas/mathematics/college/qmb770lo21ypbr27fgy14e97o87wdwlmzl.png)
So first we need to find the second central moment like this:
![E(X^2)=\int_(a)^b (x^2)/(b-a)dx = (1)/(3(b-a)) x^3 \Big|_a^b \](https://img.qammunity.org/2020/formulas/mathematics/college/immdukk6di1e4lc7rx79k0pb5kklr8epjv.png)
![E(X) = (b^3 -a^3)/(3(b-a))=((b-a)(b^2 +ab +a^2))/(3*(b-a))=(b^2+ab+a^2)/(3)](https://img.qammunity.org/2020/formulas/mathematics/college/4k048bj5ts6i4kghk7vf4fgktpqrbo38hr.png)
And now we can find the variance like this:
![Var(X) =(b^2+ab+a^2)/(3) -[(b+a)/(2)]^2](https://img.qammunity.org/2020/formulas/mathematics/college/wg9i5pvh7mqej2jowbeheyh2x0vywo3ir0.png)
![Var(X)=(4b^2 +4ab +4a^2 -3b^2-3a^2-6ab)/(12)=(b^2 -2ab +a^2)/(12)=((b-a)^2)/(12)](https://img.qammunity.org/2020/formulas/mathematics/college/45fla3ilzdmqytazkrtwzh6kyw1xpvmlmw.png)
c)
![F(X)=\int_a^x (1)/(b-a) dr =(r)/(b-a) \Big|_a^x \ =(x-a)/(b-a)](https://img.qammunity.org/2020/formulas/mathematics/college/dd09y4cxjb70l1qx9urylj8lhdqj91tujs.png)
Explanation:
For this case we assume that
![X \sim Unif(a,b)](https://img.qammunity.org/2020/formulas/mathematics/college/yplo5f7a369faxrd8ju133l53r9fyd6skc.png)
And the density function is given by
![f(X)=(1)/(b-a)](https://img.qammunity.org/2020/formulas/mathematics/college/3u4cf7m7l00132lqytx89rpmby68v2r8a7.png)
Part a
In order to find the expected value we need to do the following integral:
![E(X)=\int_(a)^b (x)/(b-a)dx = (1)/(2(b-a)) x^2 \Big|_a^b \](https://img.qammunity.org/2020/formulas/mathematics/college/wj41t4nnmuzn1m4f4bddnrbnn6sgdt54cx.png)
![E(X) = (b^2 -a^2)/(2(b-a))=((b-a)(b+a))/(2*(b-a))=(b+a)/(2)](https://img.qammunity.org/2020/formulas/mathematics/college/v91gqqkc8nak8rx79m0w4n6tf31ovxzrjv.png)
And yes agree with the intuition since is the middle value of the interval (a,b)
Part b
For this case we need to use the definition of variance:
![Var(X) =E(X^2) -[E(X)]^2](https://img.qammunity.org/2020/formulas/mathematics/college/qmb770lo21ypbr27fgy14e97o87wdwlmzl.png)
So first we need to find the second central moment like this:
![E(X^2)=\int_(a)^b (x^2)/(b-a)dx = (1)/(3(b-a)) x^3 \Big|_a^b \](https://img.qammunity.org/2020/formulas/mathematics/college/immdukk6di1e4lc7rx79k0pb5kklr8epjv.png)
![E(X) = (b^3 -a^3)/(3(b-a))=((b-a)(b^2 +ab +a^2))/(3*(b-a))=(b^2+ab+a^2)/(3)](https://img.qammunity.org/2020/formulas/mathematics/college/4k048bj5ts6i4kghk7vf4fgktpqrbo38hr.png)
And now we can find the variance like this:
![Var(X) =(b^2+ab+a^2)/(3) -[(b+a)/(2)]^2](https://img.qammunity.org/2020/formulas/mathematics/college/wg9i5pvh7mqej2jowbeheyh2x0vywo3ir0.png)
![Var(X)=(4b^2 +4ab +4a^2 -3b^2-3a^2-6ab)/(12)=(b^2 -2ab +a^2)/(12)=((b-a)^2)/(12)](https://img.qammunity.org/2020/formulas/mathematics/college/45fla3ilzdmqytazkrtwzh6kyw1xpvmlmw.png)
Part c
In order to find the cumulative distribution function we just ned to do the following integral:
![F(X)=\int_a^x (1)/(b-a) dr =(r)/(b-a) \Big|_a^x \ =(x-a)/(b-a)](https://img.qammunity.org/2020/formulas/mathematics/college/dd09y4cxjb70l1qx9urylj8lhdqj91tujs.png)